Macroeconomic Dynamics in Four Selected New Member States of the EU - Pasquale Foresti; Ugo Marani; Giuseppe Piroli (Economics and Econometrics Research Institute (EERI), 2013)
In this paper, we employ a block structured near-vector autoregression in order to compare the reactions to euro-area shocks in four New Member States (Bulgaria, Hungary, Czech Republic and Romania) and in the Old Member State of the EU. Thanks to the methodology adopted we also study the effects of national economic policies and their reactions to national shocks in each New Member State. Our analysis highlights that possible asymmetric effects of the ECB's monetary policy cannot be excluded and that the potential accession of the New Member States may increase the level of fiscal indiscipline in the eurozone.
Keywords: E52; E61; F33; F36; 330; Monetary Union; Monetary and Fiscal Policies Interaction; Economic Shocks